Seasonal Variation on The Prevalence and Molecular Characterization of Trypanosoma species from Rodents Trapped in Kilombero District, Tanzania - Amani Juma; Abduli Katakweba; Elisa Mwega; Julius Medardus (Universitas Airlangga, 2025)
Background: Trypanosomiasis is a disease mainly encountered in tropical regions and is significant to both humans and animals. Rodents and their fleas have been found to play a major role in the transmission of trypanosomiasis to humans. Purpose: This study aimed to examine the seasonal variation and molecular characterization of Trypanosoma species from rodents in Kilombero. Method: The study employed a cross-sectional design. A total of 387 rodents were captured, and anesthetized with Diethyl Ether to collect blood, spleen, and liver. Rodent tissues were tested with conventional PCR and sequencing to target the 18S rRNA and ITS1 genes. Results: The most prevalent species was Mastomys natalensis 82.43% (319/387), followed by Rattus rattus 16.79% (65/387), Gramomys spp. 0.52% (2/387), and the least captured species Lemnscomys spp. 0.26% (1/387). Overall microscopic prevalence was 38.76% (n=150/387), and PCR indicated prevalence of Trypanosoma spp. to be 6.28% (n=10/159). Male rodents had a higher molecular prevalence of Trypanosoma spp., and a higher molecular prevalence of Trypanosoma spp. was observed in the dry season. Conclusion: Detection of T. lewisi from the rodents shows the public health significance in the study area. As a result, it is critical to use prevention and control measures in rodents to minimize potential human exposure within the area.